MEDIA COMPOSITION TO SPURING GROWTH OF THE REVOCATION Scorodocarpus borneensis Becc. - Vona Septiani Putri; M. Mardhiansyah; Evi Sribudiani (Jurnal Ilmu Ilmu Kehutanan, 2021)
Scorodocarpus borneensis becc. is one of the type that is increasingly endangered in natural forests. Borneensis is a special type of wood, especially in Riau, so it is used as a raw material for community industry such as shipbuilding, masts and door frames. The cultivation efferts of resulted in the use wood in nature as a place for the preparation of wood, the effect of planting media composition on growth of Scorodocarpus bornensis Becc. the composition of the best growing media for growth of S.bornensis Becc. Extract the experiment was done by using complete randomized design (CRD) consisting of 4 treatments. Each treatment consisted of 3 replications and used 10 replications each time, with a total total of 120 pieces. Response measured to see the influence of S.bornensis Becc. Revocation on seedling growth is the percentage of seedling life, high seedling increase, increase in the number of leaves on seedlings, dry weight and top root ratio. The difference in the composition of the planting media affects the growth S.bornensis Becc. On average media compositions (clay + trichokompos 1: 1) with the finest results. The P1 (clay + trichokompos 1: 1) treatment showed the best result as a media composition S.bornensis becc. are percentage of live seedlings 93,3 %, high growth of 20,63 cm, and dry weight of 7,48g.